A writter in New York. Libertella from a distance (El Taco en la Brea, 2021)
Shortly after being awarded the Paidós Novel Prize for El camino de los hiperbóreos (1968), Héctor Libertella wins the scholarship to participate in the «Writers Seminar» at the University of Iowa. This experience begins an itinerary that transports the writer from Bahía Blanca to New York, to the world, to his last room in Buenos Aires. During this trajectory, the writer finds «there», the meanings of «here» and embodies them in writing. My critical reading dis- cusses the notions of «distance», «space» and «spatiality» in Héctor Libertella’s writing and in his figurations as a writer, since these concepts fruitfully saturate his literary project while distance as position, as equidistance be- tween spaces, times or subjectivities, and in practices and speeches, as a path, spatialities and temporalities, trans- forms fixations and hierarchies. Libertella defined his adventure and his practice as a writer according to what has been seen, read, written, performed and projected, on what he discards, inscribes and displaces the poetics of a programe of writing that is laid out as an unpredictable game of associations and dissociations
Keywords: Libertella; distance; itinerance; excess; ghost